Long-term diuretic medication is an independent predictor of posthepatectomy liver failure - Betzler, Alexander; Betzler, Johanna; Bogner, Andreas; Walther, Elene; Rahbari, Mohammad; Reissfelder, Christoph; Riediger, Carina; Weitz, Jürgen; Rahbari, Nuh N.; Birgin, Emrullah (Journal of gastrointestinal surgery, 2025)
Background - Posthepatectomy liver failure (PHLF) is the most fatal complication after liver resection, particularly in patients with comorbidities. This study aimed to assess the effect of long-term medication on PHLF incidence after open liver resections. - Methods - A retrospective analysis of 682 patients who underwent elective open hepatectomies between 2008 and 2015 at 2 academic centers was performed. Preoperative, intraoperative, and postoperative data were collected, including long-term medication. The risk factors for the development of PHLF and other postoperative complications were evaluated using univariate and multivariate logistic regression analyses. - Results - PHLF occurred in 81 patients (11.9%), with a higher incidence in patients taking diuretics as long-term medication than in those not taking diuretics (17.7% vs 5.3%, respectively; P <.001). Diuretic use was identified as a strong independent risk factor for PHLF (odds ratio [OR], 3.8 [95% CI, 2.1-7.0]; P <.001), alongside liver cirrhosis (OR, 3.8 [95% CI, 1.9-7.6]; P <.001), primary liver malignancies (OR, 3.8 [95% CI, 1.6-9.3]; P <.001), major hepatectomies (OR, 3.1 [95% CI, 1.7-5.7]; P <.001), and long operating time (OR, 4.2 [95% CI, 2.4-7.2]; P <.001). Patients with long-term diuretic intake were older, had higher body mass indices, and had more comorbidities, including liver cirrhosis. - Conclusion - Long-term diuretic use is associated with a significantly increased risk of PHLF after open hepatectomy.
Online verfügbar: 26. März 2025, Artikelversion: 4. April 2025
Gesehen am 12.06.2025